Low-intensity blood flow restriction calf muscle training leads to similar functional and structural adaptations than conventional low-load strength training: A randomized controlled trial - Gavanda, S.; Isenmann, E.; Schlöder, Y.; Roth, R.; Freiwald, J.; Schiffer, T.; Geisler, S.; Behringer, M. (PLOS ONE, 2020)
he purpose of this study was to investigate whether a six-week, twice weekly resistance training (4 sets at 30% 1-RM until failure) with practical blood flow restriction (BFR) using 7cm wide cuffs with a twist lock placed below the patella is superior to training without BFR (NoBFR) concerning muscle mass and strength gains in calf muscles.